Understanding Cardiovascular Events With JAK Inhibitors: Tofacitinib Reduces Synovial and Vascular Inflammation but not the Prothrombotic Effects of Inflammatory Cytokines on Endothelium - Aliki Zavoriti; Pierre Miossec (ACR Open Rheumatology)
Objective Inflammation drives cardiovascular disease in rheumatoid arthritis (RA). Treatment with tofacitinib, a JAK1/JAK3 inhibitor, is associated with increased cardiovascular events in patients with RA. Here, we determined its effects on cytokine production during interactions between immune cells at the synovial and vascular levels and its impact on endothelial activation and coagulation during inflammation. Methods Activated human peripheral blood mononuclear cells (PBMCs) were cocultured with RA synoviocytes or endothelial cells (ECs) mimicking the cellular interactions in synovium and vessels responsible for cytokine production. A dose‐response of tofacitinib was tested on interferon γ, interleukin (IL) 17A, IL‐10, IL‐6, and IL‐1β, and cytokine production was measured by enzyme‐linked immunosorbent assay at 48 hours. Endothelial activation was induced with IL‐17A and tumor necrosis factor (TNF) or on contact with PBMCs. Shortly after tofacitinib treatment, the expression of EC activation markers, specifically IL‐6, IL‐8, vascular cell adhesion molecule 1 (VCAM‐1), and E‐selectin, and of coagulation, including tissue factor and thrombomodulin, was assessed by real‐time polymerase chain reaction. Results Tofacitinib differentially inhibited production of IFNɣ, IL‐17A, and IL‐10 from PBMC cocultures with RA synoviocytes or ECs (all P < 0.001). In cocultures with ECs, tofacitinib reduced further IL‐6 and IL‐8 production (both P < 0.001). In ECs activated by TNF/IL‐17A or indirectly via contact with activated PBMCs, tofacitinib decreased IL‐6 upregulation but not that of IL‐8, E‐selectin, or tissue factor. Thrombomodulin was significantly decreased. VCAM‐1 was greatly induced with a higher dose of tofacitinib in ECs incubated directly with added inflammatory cytokines (P < 0.05) or released by interaction with activated PBMCs (P < 0.001). Conclusion Tofacitinib inhibits synovium and vascular inflammation but fails to prevent the prothrombotic effects of inflammatory cytokines on ECs.